2021
DOI: 10.1177/1368430220987595
|View full text |Cite
|
Sign up to set email alerts
|

Gender/sex diversity beliefs: Scale construction, validation, and links to prejudice

Abstract: Prejudice against or affirmation of gender/sex minorities is often framed in terms of beliefs about the ontology of gender/sex (i.e., what gender/sex is), or gender/sex diversity beliefs. We constructed the Gender/Sex Diversity Beliefs Scale (GSDB) to assess ontological beliefs about the nature of gender/sex, including essentialist and social constructionist beliefs, and validated the GSDB across a series of studies. In Study 1 ( N = 304), we explored the factor structure of the GSDB and found evidence of asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 74 publications
(120 reference statements)
1
24
0
Order By: Relevance
“…Some initial evidence suggests that when considering all genders, an identity‐aware approach may be more effective than an identity‐blind approach. To illustrate, affirmation of different gender identities, which parallels gender awareness in its emphasis on celebrating gender‐related diversity, is associated with less prejudice against gender minorities (e.g., transgender and nonbinary individuals; Schudson & Van Anders, 2022). Furthermore, a recent set of experiments demonstrated that including gender pronouns in an organization's employee biographies—an example of how gender awareness can be implemented—increased LGBT participants’ trust and anticipated comfort in the organization (Johnson et al., 2021).…”
Section: Review Of Outcomes Associated With Multicultural and Colorbl...mentioning
confidence: 99%
“…Some initial evidence suggests that when considering all genders, an identity‐aware approach may be more effective than an identity‐blind approach. To illustrate, affirmation of different gender identities, which parallels gender awareness in its emphasis on celebrating gender‐related diversity, is associated with less prejudice against gender minorities (e.g., transgender and nonbinary individuals; Schudson & Van Anders, 2022). Furthermore, a recent set of experiments demonstrated that including gender pronouns in an organization's employee biographies—an example of how gender awareness can be implemented—increased LGBT participants’ trust and anticipated comfort in the organization (Johnson et al., 2021).…”
Section: Review Of Outcomes Associated With Multicultural and Colorbl...mentioning
confidence: 99%
“…To improve model fit, we followed the procedure outlined in Schudson & van Anders ( 2022 ) to further refine our model. Based on the Study 1 EFA, we included items that fulfilled three criteria: (1) high factor loadings (> 0.50), (2) loaded strongly onto a single factor (at least 0.15 difference between the highest factor loading and the second highest), and (3) measured unique facets of household labor.…”
Section: Resultsmentioning
confidence: 99%
“…Beliefs and attitudes toward sexual minority individuals and gender minority individuals are separate but intertwined for many reasons, not the least of which is that many gender minority people identify as a sexual minority (Galupo, Henise, & Mercer, 2016); all sexual minority people effectively buck heteronormative expectations of appropriately gendered behavior by virtue of homosexual desires and/or practices; and discourse on the etiology of gender nonconformity maps onto much of the discourse about the etiology of sexual orientation (Meadow, 2018). Therefore, future work in this domain should retain a conceptual and practical distinction between beliefs about sexual orientation and gender identity but examine gender identity beliefs alongside and independent of beliefs about sexual orientation (Schudson & van Anders, 2020; van Anders, 2015).…”
Section: Discussionmentioning
confidence: 99%